Forgive Them, as They Do Not Know What They Are Saying: A Passing Thought about Chapter Six in Reply to Owiti and Ogutu’s Responses . - M. O’kubasu , Duncan (Kabarak Journal of Law and Ethics, 2021)
This brief response considers the rejoinders to the paper titled “Ruinous Judicial Activisms: What a Solemn Scrutiny of the Ruling of Justice Mumbi Ngugi in the Moses Kasaine Lenolkulal Reveals.” It examines the responses it has elicited to identify areas of convergence and divergence both with the paper and with each response. In the end, it suggests that jurists should look at the purport of Chapter Six of Kenya’s Constitution, as it now stands, not in one way only as there can be temptations to misuse it.